PENGARUH KOMPETENSI MANAJERIAL, SUPERVISI DAN SOSIAL KEPALA SEKOLAH TERHADAP MUTU PENDIDIKAN DI SMP NEGERI SE-KOTA BIMA - Yati Auliah; I Nyoman Nugraha Ardana Putra; Idha Novianti (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The aims of this study were to: (1) analyze the effect of principal managerial competence on the quality of education in public junior high schools throughout the city of Bima; (2) analyzing the influence of the supervisory competence of the principal on the quality of education in public junior high schools throughout the city of Bima; (3) analyzing the influence of the principal's social competence on the quality of education in public junior high schools throughout the city of Bima; and (4) analyze the dominant influence on the quality of education in public junior high schools throughout the city of Bima. Theoretically, the results of this research are expected to add insight into the study of science in the field of human resources and hopefully it can be used as a complementary reference for other similar studies in the field of human resources and the quality of education. Practically, the results of this study can provide input, among others, as material used in formulating policies in appointing school principals in a competency-based professional manner, and as material for further studies in the context of implementing school principals' performance evaluations in improving the quality of education in Bima Regency. The population of this study were all State Civil Apparatus (ASN) teachers with the lowest qualification rank/class III-c serving in public junior high schools throughout the city of Bima as many as 127 people and the research sample as many as 100 people after calculations using the Slovin formula and random sampling technique. After analyzing the validity and reliability of the instrument, the data was analyzed using simple linear regression. The results of the study concluded that managerial competence in addition to having a positive and significant influence on the quality of education at state junior high schools throughout the city of Bima is also the variable with the most dominant influence on the quality of education. Supervision competence has a positive and significant influence on the quality of education in public junior high schools throughout the city of Bima, and social competence has a positive and significant influence on the quality of education in public junior high schools throughout the city of Bima. Therefore, the principal as a leader in the school must have and hone competence, especially managerial competence in developing the quality of education, including the supervisory competence and social competence of the principal.